The Philosophical Foundations Of Holistic Education In The 21st Century (Challenges And Obstacles To The Development Of Islamic Education) - Mahmudulhassan, Mahmudulhassan; Elbanna, Mariam; Abuzar, Muhammad (Sekolah Tinggi Agama Islam Muhammamdiyah Blora, 2025)
This article discusses the philosophical foundations of holistic education in the 21st century with a focus on the challenges and obstacles in its development in the context of Islamic education. The background of this research is based on the urgent need for a comprehensive and balanced approach to education in the face of the complexity of modern times marked by technological developments, moral crises, and the fragmentation of science. The GAP of this research lies in the lack of in-depth studies that integrate the holistic paradigm with the values of Islamic education philosophically and applicatively in facing the challenges of globalization and modernization. This research uses a qualitative approach with the library research method, which examines the literature on holistic education philosophy and Islamic educational thought from various primary and secondary sources. The benefit of this research is that it makes a conceptual contribution to the development of a more complete, transformative, and contextual Islamic education paradigm, as well as a reference for policymakers and education practitioners in designing a learning system that is in line with spiritual, intellectual, and social values of the 21st century.